Design and Value Analysis of Configuration &Activation System Based on SOA - Yongqiang Li; Junfeng Hu (Dianxin kexue)
In order to seize market opportunities, rapid service fulfillment and high quality network service become the operators' urgently needs to solve problems. In order to achieve the customer service end-to-end rapid fulfillment, a network data configuration activation method based on SOA was proposed, and the network resource data configuration & activation system was constructed, the one-click end-to-end service fulfillment was realized. By this method, not only greatly improves the efficiency of service fulfillment, also avoids the artificial network data configuration errors in the process of service fulfillment.